Factors Associated with Intention in Performing Foot Care Using the Theory Of Planned Behavior in Type 2 Diabetes Mellitus Patients - Yunita, Waode; Narmawan, Narmawan; Jasmin, Muh. (Adi Husada Nursing Journal, 2023)
One of the efforts to prevent complications of diabetic neuropathy in diabetic patients is foot care such as washing the feet every day, drying and oiling them, examining the feet for foot ulcers and signs of pre-ulceration, and wearing well-closed footwear at home. or outside the house. In performing foot care, DM sufferers must have strong intentions and beliefs so that they can run it well. This study aimed to determine the factors related to the intention to perform foot care using the theory of planned behavior at the UPTD of the Poasia Health Center, Kendari City. This study used a correlation design with a cross-sectional study approach involving 32 samples. The sampling technique used was accidental sampling. The instrument used is a questionnaire. Data analysis using Spearman correlation test. The results showed that there was no relationship between attitudes (direct = 0.9, indirect = 0.11), subjective norms (direct = 0.058 and indirect = 0.165) and behavioral control (direct = 0.022 and indirect = 0.037) on the intention to perform foot care in Type 2 DM patients. Further research should examine respondents who have understood or understood the importance of DM foot care. It is recommended that respondents and families still need foot care daily to prevent wound complications.